A Study Of Consumer Preference Towards Cocktail & Mocktail Consumption in Ahmedabad for Generation Z - Harsh; Pinkal; v, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examined the relationship between age group and various factors influencing beverage preferences, focusing on attributes such as social media influence, health consciousness, taste, and customization. Using descriptive methods, ten hypotheses were tested to determine whether age significantly influences preferences for beverage type, ingredients, and consumption behavior. The results showed no statistically significant relationship at the 0.05 level between age and the factors studied, although strong correlations were observed for preferences such as natural ingredients, customization, and situational relevance, indicating universal appeal across demographics. Future research could explore other demographic factors, lifestyle influences, and cross-cultural comparisons to deepen insights into beverage preferences This study examines the relationship between age groups and various factors influencing beverage preferences, focusing on attributes such as social media influence, health consciousness, taste, and customization. Ten hypotheses were tested to determine if age significantly impacts preferences for beverage types, ingredients, and consumption behaviors. Results indicated no statistically significant associations at the 0.05 level between age and the factors studied, although strong correlations were observed for preferences like natural ingredients, customization, and situational relevance, suggesting universal appeal across demographics. These findings imply that age may not be a primary determinant in beverage choices, with broader motivations such as health benefits, taste, and customization playing a more influential role. The study’s practical implications suggest that brands in the beverage industry could benefit from emphasizing cross-generational appeals, focusing on product qualities that resonate universally rather than tailoring campaigns solely based on age. The theoretical implications support a shift toward understanding intrinsic product qualities and universal consumer motivations over age-specific marketing. Future research could explore other demographic factors, lifestyle influences, and cross-cultural comparisons to deepen insights into beverage preferences. Overall, the study offers a nuanced understanding of consumer behavior in beverage selection, highlighting the potential for brands to build inclusive marketing strategies based on universal motivations.